INVESTIGATIONS ON ONOSMA HISPIDUM WALL ROOT EXTRACTS FOR IN-VITRO ANTIDIABETIC, PROLIFERATIVE AND CYTOTOXIC EFFECTS - M.Asghar; M.Islam; H.Saeed; F.Imtiaz; B.Saleem; Z.Saleem; S.Qamarand M.Iqtedar (Journal of Animal and Plant Sciences, 2018)
Theaimofthisstudywastoinvestigatetheimpactofvariousextractsofrootsof Onosma hispidumforanti-diabetes, proliferativeandcytotoxiceffectsusing in-vitroassays.Phytochemicalscreeningofpowderandextractswasdoneby employing standard methods. Anticancer activity was assessed by using MTT (3-(4,5-dimethylthiazol-2-yl)-2,5- diphenyltetrazoliumbromide)andshorttermproliferationassayonHepG2cellline.Theantidiabeticpotentialwas determined byusing alpha-amylase inhibition assayand non-enzymatic glycosylation of haemoglobin assay. Data suggested that primary (CHO; 68.06 ± 0.19 and Proteins; 9.48 ± 0.27) and secondary metabolites (mg/g); max. Flavonoids (47.55 ± 0.13) in aqueous extract, max. Polyphenols (107.77 ± 0.57) in Pt. ether extract and max. glycosaponins(94.5±0.51)inchloroformextract,exhibitedvariationsamongvariousextractsobtainedfromrootsof Onosma hispidum.Petroleumetherandaqueousextractsexhibitedsignificantimpact(p<0.05)ontheproliferationof HepG2celllinesatdifferenttimepointscomparedtocontrol,whileincaseofMTTassay,nosignificantresults(p>0.05) wereobtainedafterovernightincubation.Improvedantidiabeticactivitywasexhibitedbypetroleumetherextract(70% inhibition)ascomparedtoAcarbosestandardusingalpha-amylaseinhibitionassay,withanIC of80µg/ml.Innon- 50 enzymatic glycosylation of haemoglobin assay, better potential was shown by chloroform extract with an IC of 50 35µg/ml,whencomparedtoastandard-Tocopherol.Thisstudyrevealedthattherootsof Onosma hispidumpossess nutritionalvalueandantidiabeticproperties,alongwithsignificantimpactoncell(HepG2)proliferation. and anti-mutagenic effects (Urquiaga and Leighton,
Keywords: Onosma hispidum; In-vitro; Polyphenols; Antidiabetic; Anticancer.